Analysis of connecting rod fracture using finite element analysis - Ahmad Ridzuan, Ibrahim (2010)
This thesis presents an analysis of connecting rod fracture using Finite Element Analysis. The connecting rod is one important part in an engine. In this task, connecting rod of the Proton Wira 1.5 is used. After measurements were taken, connecting rods were drawn using SolidWorks software and save in 'IGES' format. Then, the drawing of connecting rod (IGES format) imported into ALGOR software. In this software, can makes analysis to connecting rod and thus to know the stress and strain that occur on the connecting rod. This analysis uses a different mesh of 100% and 80%. It aims to get more precise results. The smaller the percentage of mesh used the more accurate results will be. Failure of connecting rod occurs depend on compared value stress von mises and yield strength of materials. Failure occurs if value stress von mises higher compared yield strength of material. The result shows failure of connecting rod occurs while applied load at 26kN if used steel as material and 24kN if used aluminium alloy. The entire project involves various processes such as process design and analysis.